2016
DOI: 10.1021/acs.iecr.6b01778
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Characteristics and Design of Transverse Jet Mixers with Multiple Orifices

Abstract: We investigated and compared the turbulent characteristics of two-liquid mixing in single-orifice and multiorifice-impinging transverse (MOIT) jet mixers through large eddy simulations and the planar laser-induced fluorescence technique. Our focus is on evaluating the roles played by the interactions among the jets in the mixing intensification. The turbulent vortex structures, time-averaged mean concentration distributions, root-mean-square of the concentration fluctuations, probability density function, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Firstly, numerical prediction accuracy is evaluated. As the grid sensitivity analysis has been carried out in our previous work, 26 here we only validate the simulation results from the wall y + value discussion, power spectral density (PSD) analysis, and time‐averaged concentration distribution comparison.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, numerical prediction accuracy is evaluated. As the grid sensitivity analysis has been carried out in our previous work, 26 here we only validate the simulation results from the wall y + value discussion, power spectral density (PSD) analysis, and time‐averaged concentration distribution comparison.…”
Section: Resultsmentioning
confidence: 99%
“…The SIMPLE algorithm is adopted for pressure–velocity coupling, and the bounded central differencing method is used for the spatial discretization of the momentum, turbulent kinetic energy, and concentration. Time step is set to 0.0002 s. The mesh generation method, boundary condition setting, and grid sensitivity analysis has been discussed in our previous work 26 and is also adopted in this work.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of the Velocity Ratio on Mixing and the Crystallizer. Luo et al 9 have found in their study that the ratio of jet and cross flow velocity (r) is the main factor affecting the mixing. Although water was used as the working medium in the study, they did not consider the density and viscosity differences between particles, the solvent, and the antisolvent.…”
Section: Comparisons With Experiments Datamentioning
confidence: 99%
“…Therefore, secondary nucleation caused by impellers would lead to broad CSD and a small crystal size. Compared with tank crystallizers, tubular crystallizers (such as impingement jets ,,, and coaxial nozzle crystallizers) do not have such mechanical collisions. Due to uniform supersaturation and residence time distribution, it can produce crystals with a narrower CSD.…”
Section: Introductionmentioning
confidence: 99%